The effect of pelleting parameters on phytase stability and pellet quality - Saensukjaroenphon, Marut (Kansas State University, 2019)
Phytase is a phosphohydrolytic enzyme that releases phosphorus from phytate in animal feed. Temperature and moisture content have been identified as two factors that can influence enzyme inactivation. Thus, exogenous phytases were developed to tolerate the high temperature reached during pelleting and the low pH in the stomach. It is hypothesized that there are many factors that can account for phytase denaturing during the pelleting process, such as pellet mill model, die length to diameter ratio (L:D), conditioner or die retention time, and steam quality. Moreover, phytase may be further degraded in feed samples if moisture is left in the sample and the sample is not properly stored prior analysis. The objectives of this dissertation were to determine the effects of pelleting parameters, moisture content in the mash feed or sample, sample preparation, storage condition or storage time of the sample prior to analysis, and phytase analysis method on phytase stability or pellet quality. The first experiment was conducted to evaluate the effect of the following factors: cooling method, sample preparation, storage condition and storage time on phytase denaturation after steam conditioning or pelleting. The results of the first experiment indicated that freeze-drying, vacuum sealing and freezing were not required when the sample is analyzed within 3 weeks of production. The pellet temperature, pellet moisture and cooling time after the pellet die did not affect phytase stability. The second experiment investigated mash moisture content and exposure time in feed prior to pelleting and the subsequent effect on phytase denaturation post-pelleting. The results of the second experiment indicated that the stability of phytase was not affected when feed was stored in a bin up to 2 hr. prior to pelleting. The added water in the mash feed did not affect the degradation of Trichoderma reesei phytase when the feed moisture did not exceed 13%. Additionally, the ELISA or EN ISO method could be used in the laboratory to determine Trichoderma reesei phytase stability. Increasing moisture content of mash feed by 0.6% did not improve pellet quality. The third experiment was conducted to determine the effect of die retention time on phytase stability. The results of the third experiment indicated that the phytase was stable up to 88°C. The hot pellet temperature should be measured when enzymes are added to the feed to help monitor phytase stability. The die L:D is one of the most important factors for pellet quality. Increasing die retention time by reducing production rate improved pellet quality but may reduce phytase stability. The fourth and fifth experiments were designed to determine the effect of corn starch inclusion level, fines inclusion level, die thickness and conditioning temperature on pellet quality. The results demonstrated that increasing conditioning temperature or die thickness increased pellet quality. Increasing the ratio of corn starch to corn protein resulted in lower PDI when the diet contained more than 60% ground corn. When a diet contained less than 1.5% oil, fines returned from the sifter improved pellet quality.
Keywords: phytase stability; die retention time; particle size; pellet quality; extruded corn; cooling method